Is more inclusive more effective? The “new-style” public distribution system in India - Kishore, Avinash; Chakrabarti, Suman (International Food Policy Research Institute, 2015)
This paper tries to account for the changes in household consumption patterns associated with the change in PDS policy in these states using data from household consumption surveys by the National Sample Survey Organization (NSSO). These data show improvement in the coverage of TPDS and average offtake of grains from fair-price shops between 2004/2005 and 2009/2010 across all states of India. However, the increase in coverage and offtake was significantly higher in four out of these five states than in the rest of India. An average household in these states purchased 3 kg more rice per month from fair-price shops than its counterpart in nontreated states as a result of more generous TPDS policies backed by administrative reforms. The increase in consumption of PDS rice was the highest in Chhattisgarh, the poster state of public distribution system reforms. Households in Chhattisgarh used money saved on rice to spend more on pulses, edible oil, vegetables, sugar, and nonfood items. We also find evidence that making TPDS more inclusive and more generous is not enough unless it is supported by administrative reforms to improve grain delivery and control diversion to open markets.